Pengaruh Perilaku Keuangan Terhadap Minat Investasi Pada Nasabah Bank Syariah Indonesia KCP Johan Pahlawan - Affiqah Hunaina; Chairiyaton Chairiyaton (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Investment interest is an individual's desire to invest to achieve long-term financial goals. The general goal of investing is to generate passive income, capital growth, or both. The purpose of this research is to see whether financial behavior influences investment interest among BSI KCP Johan Pahlawan customers. This research uses quantitative methods with a descriptive type. The population in this study were all customers of Bank Syariah Indonesia Johan Pahlawan Sub-Branch Office. The sample used in this research was 100 customers, taken from this population. The data collection technique in this research was to use a questionnaire which was distributed to the entire research sample. The data analysis technique used is simple linear regression analysis, with the help of SPSS software. The collected questionnaire data will be analyzed using simple linear regression analysis techniques to test the research hypothesis. SPSS software was used to assist statistical calculations in analyzing the data. The results of this research show that financial behavior has a positive and significant influence on the investment interest of the Johan Pahlawan community, this is proven by the acquisition of a sig of 0.00 < 0.05. In other words, Johan Pahlawan's financial behavior in managing their personal finances has an impact on their interest in investing.